Afro-Peruvian Spanish: Linguistic Acctitudes of the Afro-Peruvian from El Carmen - Jimenez Lizama, Pamela (2017)
This preliminary research deals about the linguistic attitudes of Afro-Peruvians in the district of El Carmen, Chincha (Ica), towards the Afro-Peruvian Spanish spoken in El Carmen and other Spanish varieties in Peru. The mentalist theoretical approach (González, 2009; Zamora, 2015) is applied to focus on the linguistic attitudes. The methodology used is quantitative and qualitative. Twelve collaborators were interviewed taking into account the variables of sex, age and degree of instruction. As a result, it was found that young people from El Carmen tend to value positively the Lima dialectal variety (50%). In contrast, the negative assessments of Afro-Peruvians are related to the varieties of Spanish in the Andean region, a situation that is accentuated in young people (50 %). In addition, it is concluded that the elision of segments in pronunciation is stigmatized in this district.